(untitled) (Annals of Medical Research, 2021)
Aim: To investigate dental problems of Syrian refugees in southeast Turkey and assess the burden of their dental healthcare costs to government. Material and Methods: A retrospective study included dental records of Syrian refugees who applied to Adıyaman Dental Hospital (ADH), were compared with Adıyaman public by years.Results: In 2012, the most common treatments were tooth extraction and complicated tooth extraction, the total dental care cost of such refugee patients was 3,082.14 and the median cost per refugee was 4.43. The most common treatment provided to both the Adıyaman public and Syrian refugees in 2017 was dental filling. In the same year, total dental care cost of refugees was 603,303.69, the median cost per refugee was 22.20. The total dental care cost of the Adıyaman public was 3,869,524.96, the median dental care cost in Adıyaman public was 17.95 for one person in 2017.Conclusions: Dental problems of Syrian refugees and the financial burden of their dental healthcare to the government significantly increased.Keywords: Refugee; dental care cost; Syrian; immigrant; treatment; budget